Fabrication of the Superhydrophobic Surface on Magnesium Alloy and Its Corrosion Resistance. Issue 11 (November 2015) - Zhang, Fen; Zhang, Changlei; Song, Liang; Zeng, Rongchang; Li, Shuoqi; Cui, Hongzhi
Abstract : The superhydrophobic surface was fabricated on the AZ31 alloy by the combination of the hydrothermal treatment method and post modification with stearic acid. The superhydrophobic surface showed a static water contact angle of 157.6°. The characteristics of the coatings were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR). The corrosion resistance of the superhydrophobic coatings was investigated by potentiodynamic polarization test and electrochemical impedance spectroscopy (EIS). The results revealed that the superhydrophobic coatings, characterized by petal-like structure significantly improved the corrosion resistance of the AZ31 alloy.